2010
DOI: 10.4028/www.scientific.net/amr.160-162.1445
|View full text |Cite
|
Sign up to set email alerts
|

The Construction and Analysis of Eutrophication Model for Caohai of Dianchi Lake

Abstract: The aquatic ecosystem of lake is a complex open systems, this study that is based on the principles of maximum flux selects Caohai as the object, we apply complex systems analysis to construct eutropication model which is suitable for local conditions and select a larger time scale and control parameters to simulate the eutrophication status to find out the main factors and to put forward reasonable proposals for giving out optimal control techniques. This model can be expanded in time scale, spatial scale and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Many studies focused on fertilization and quality of soil, water, and sediment have been reported (Lv et al, 2011;Mao et al, 2011;Shi et al, 2011;Yang et al, 2010). For the key source of agricultural pollution, many studies have used models to estimate the actual circumstances of NPS pollution (Wu et al, 2012;Li et al, 2012;Shi et al, 2005).…”
mentioning
confidence: 99%
“…Many studies focused on fertilization and quality of soil, water, and sediment have been reported (Lv et al, 2011;Mao et al, 2011;Shi et al, 2011;Yang et al, 2010). For the key source of agricultural pollution, many studies have used models to estimate the actual circumstances of NPS pollution (Wu et al, 2012;Li et al, 2012;Shi et al, 2005).…”
mentioning
confidence: 99%